Influence of Rib Cage on Static Characteristics of Scoliotic Spine. (19th October 2020) - Lin, Liying; Jia, Shaowei; Yang, Hufei; Li, Ye; Zhang, Shunxin; Fan, Jie; Han, Li
Abstract : Background . Scoliosis is a three-dimensional (3D) deformity of the spine, which affects the patient's appearance and may lead to abnormal heart and lung function. The rib cage is a structure composed of ribs, sternum, and costal cartilage, which plays a vital role in stabilising the thoracolumbar spine. This study investigates the influence of the rib cage on the static characteristics of the scoliotic spine. Methods . Two types of 3D finite element (FE) models with or without rib cage (from T1 to S) were established and analysed based on computed tomography (CT) images, to determine the effects of the rib cage on the static characteristics of the scoliotic spine. The FE software, ABAQUS, was used to analyse the static behaviours of scoliotic spine models under a range of loading conditions, including left side bending, right side bending, front tilt, rear supine, and vertical compression. The changes in the von Mises stress (VMS) within the intervertebral discs of spine models with or without rib cage were studied and compared. Results . After including the rib cage, the maximum VMS at the stress concentrations of the normal and scoliotic spine effectively reduced. The VMS in normal intervertebral discs was gentler than that of scoliotic ones. However, the scoliotic spine was more likely to produce large stress concentration in the intervertebral discs of scoliotic segments. Conclusions . Under the common postures, intervertebral discs of scoliotic segments are more susceptible to generate stress concentrations compared with the normal spine. The rib cage could effectively keep the intervertebral discs of scoliotic segments from further injuries. These results are of great significance for the prevention and treatment of the scoliotic spine.